Age Estimation Methods In Forensic Odontology - Duangto, Phuwadon; Janhom, Apirum; Prasitwattanaseree, Sukon; Mahakkanukrauh, Pasuk; Iamaroon, Anak (UI Scholars Hub, 2016)
Age estimation, using forensic odontology, is a crucial step for biological identification. Currently there are many methods available to predict the age of deceased or living persons, each with varying accuracy, such as a physical examination, radiographs of the left hand, and dental assessments. Age estimation, using radiographic tooth development, has been found to be a more accurate method because it is mainly genetically influenced and as such is less likely to be affected by nutritional and environmental factors. The Demirjian et al. method for dental age estimation, using radiological techniques, has long been the most common protocol used in many populations. This method, which is based on tooth developmental changes, is a straightforward process as different stages of tooth development are clearly defined. This article aims to elaborate on the Demirjian et al. method of age estimation using tooth development as a guide.